Stigma With Community Discrimination Behavior on Covid-19 Patients in Tuban - Miftahul Munir; Suhartono; Ahmad Fauziansyah; Aprilia Suryani (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
The rapid transmission of the Covid-19 virus, coupled with the circulation of social media information that cannot be verified, will impact stigma in the form of discriminatory behavior in society. This study aimed to determine the relationship between stigma and community discriminatory behavior in patients with COVID-19 at the Permata Bonang RT Perbon Tuban. This study uses a design with a Cross-sectional Study approach. The population used is part of the community in the Permata Bonang RT, with a total of 45 respondents and a sample of 40 using simple random sampling. The dependent variable is stigma, and the independent variable is discriminatory behavior. Data collection using a questionnaire sheet was analyzed using the chi-square test. The results showed that the positive stigma of society was 60% and the negative stigma of society was 40%; as for the results of discriminatory community behavior that occurred, a small number of respondents had discriminatory behavior, namely 32.5%, and some respondents who did not discriminate, namely 67, 5%. So the results obtained in this study show a relationship between stigma and community discriminatory behavior in patients with COVID-19. The results of the chi-square test evidence this; the p-value is <0.05 (p-value = 0.000), so there is a relationship between stigma and discriminatory behavior in society. Based on the results of this study, respondents are advised to keep thinking positively by providing support and motivation for positive patients for Covid-19, increasing proper knowledge about education and information based on facts so that they can be wiser in responding to current conditions.